2019
DOI: 10.1016/j.eats.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Complete Rupture of the Biceps Femoris Insertion: A Surgical Repair Technique Manuscript

Abstract: Isolated rupture of the distal biceps femoris insertion is rare. Current literature offers limited case reports and outcome measures after surgical management. We describe a knotless suture anchor fixation technique for this tear pattern. At surgery, the retracted biceps tendon and insertion site is debrided to healthy tissue, FiberTape suture (Arthrex) is passed in a Kracków fashion through the tendon, and the 2 ends of the suture are brought down to a SwiveLock anchor (Arthrex) at the anatomic insertion. Fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The majority of patients (7/8) were managed surgically with transosseous fixation, with moderate‐to‐good outcomes. Raines et al [29] describe a knotless suture anchor fixation technique for operative fixation of isolated biceps femoris tendon tears. According to published studies, patients with a distal biceps femoris rupture can be expected to return to their pre‐injury function following surgical reattachment.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients (7/8) were managed surgically with transosseous fixation, with moderate‐to‐good outcomes. Raines et al [29] describe a knotless suture anchor fixation technique for operative fixation of isolated biceps femoris tendon tears. According to published studies, patients with a distal biceps femoris rupture can be expected to return to their pre‐injury function following surgical reattachment.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed surgical technique for repair of isolated rupture of biceps femoris insertion has been described using FiberTape suture (Arthrex) and SwiveLock anchor (Arthrex). 15 A biomechanical study of repair techniques of biceps femoris 16 showed that a technique involving transosseous fibular tunnel had a higher mean failure load compared to repairs relying on suture anchors for fixation.…”
Section: Discussionmentioning
confidence: 99%
“…As the peroneal nerve is closely related to the distal biceps, femoris a neurological examination should be performed to exclude associated injury. 7 An MRI was performed a week after the injury that demonstrated a full-thickness tear of the biceps femoris just proximal to the fibular insertion with moderate soft tissue edema and a small hematoma. A short distal stump of the biceps femoris tendon was attached to the fibula head (►Fig.…”
Section: Casementioning
confidence: 99%
“…As the peroneal nerve is closely related to the distal biceps, femoris a neurological examination should be performed to exclude associated injury. 7 …”
Section: Introductionmentioning
confidence: 99%